Asuhan Keperawatan Pada Ny. S Dengan Gangguan Integritas Kulit/Jaringan Berhubungan Dengan Neuropati Perifer Dm 2 Di Igd Rsd Gunung Jati - Mahendra; Endah Sari Purbaningsih; Rizki Dian Cahyawati; Sumarni; Dikha Sazilli (MEJORA Medical Journal Awatara, 2024)
According to WHO, diabetes mellitus is a metabolic disorder characterized by increased levels of glucose in the blood (causing hyperglycemia), there are disorders of carbohydrate, fat and protein metabolism caused by damage to insulin (insulin resistance), and as a result the production and performance of insulin does not work properly. If this increase in blood glucose levels lasts for a long time and is not treated properly, this can cause complications, namely neuropathy, diabetic retinopathy, cardiovascular disease, diabetic nephropathy and diabetic ulcers. Diabetic ulcers are a complication that is difficult to treat because it is difficult for oxygen dan white blood cells to reach the tissue. One of the causes of diabetic ulcers is decreased peripheral circulation which is greatly influenced by high blood glucose levels and is closely related to peripheral arterial disease. This research aim to study and understand in depth nursing care for patients with diabetic ulcers. After applying nursing care to Ms. S patients using a case study method consisting of assessment, nursing diagnosis, intervention, implementation and evaluation. The results showed that after the wound was treated, the redness, bleeding and hematoma decreased, the wound looked clean and sterile, the problem was partially resolved, the intervention was continued with changing the bangage every day.